OBTAINING AND DETERMINING THE PURITY OF A PURE PREPARATION FOR THE "POTATOX X" VIRUS USING HELPHILTRATION METHOD (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
This in the article , KXV 's clean drug separate get for gel filtration method selected , gel chromatographic from TSK 75 gel in the column was used . The simplest, most convenient and most common method of detection in laboratory conditions - spectrophotometry method - was used to assess the concentration of viruses. The degree of purity is determined depending on the absorption of UV light of the purified viral drug using the gel chromatography method. The concentration of the purified virus was measured in a spectrophotometer of the brand "METASH-5100" at a wavelength of 220-310 nm [1]. The E 260nm 0.1% 1cm of KXV is 2.9, and the 260/280 ratio is 1.2.